ANALISIS YURIDIS TERHADAP TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK YANG BERMUATAN PERJUDIAN - Bagas Dwi Akbar; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
Online gambling crimes consist of servers made by online bookies which are often placed in countries that legalize gambling, while the problem in this research is the Legal Arrangements for Criminal Liability for Parties Who Share Channel Links in which Online Gambling Content is contained. , Second, criminal responsibility for the actions of partieswho play gambling through online channel links. Third, law enforcement policies in efforts to deal with criminal acts of online gambling information technology, the research method uses normative type research and is descriptive analysis in nature. Research results ongambling content can be held criminally responsible for violating the provisions of Article 45 paragraph (2) in conjunction with Article 27 paragraph (2) of the ITE Law, Criminal liability for perpetrators of online gambling websites must fulfill the elements of legal responsibility in efforts to tackle criminal acts of online gambling information technology in essence the criminalization policy is part of the criminal policy by using criminal law means and therefore includes part of the criminal law policy.